2009
DOI: 10.1089/jmf.2008.1114
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Alcohol Extracts of Hizikia fusiforme Sensitize AGS Human Gastric Adenocarcinoma Cells to Tumor Necrosis Factor-Related Apoptosis-Inducing Ligand-Mediated Apoptosis

Abstract: Resistance to tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis has been reported in some cancer cells, including AGS human gastric adenocarcinoma cells. Hizikia fusiforme is a commonly used brown seaweed species in Korea that possesses potent antibacterial, antifungal, and anti-inflammatory activities. In this study, we demonstrated that treatment with TRAIL in combination with subtoxic concentrations of ethyl alcohol extract of H. fusiforme (EAHF) sensitized TRAIL-resistant AG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Recently the inhibitory properties of H. fusiforme on the production of pro-inflammatory mediators and ethanol- induced cytotoxicity have been demonstrated [2,16]. Additionally, we previously reported that EAHF sensitizes TRAIL-induced apoptosis and inhibits matrix metalloproteinase activity as well as tight junction in cancer cells [4,17]. Before now, there were no reports on whether EAHF itself induces apoptosis in cancer cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently the inhibitory properties of H. fusiforme on the production of pro-inflammatory mediators and ethanol- induced cytotoxicity have been demonstrated [2,16]. Additionally, we previously reported that EAHF sensitizes TRAIL-induced apoptosis and inhibits matrix metalloproteinase activity as well as tight junction in cancer cells [4,17]. Before now, there were no reports on whether EAHF itself induces apoptosis in cancer cells.…”
Section: Discussionmentioning
confidence: 98%
“…Previous research has reported that H. fusiforme has a variety of physiological activities, such as reactive oxygen species (ROS) scavenging and lipid oxidation inhibitory effects [3]. Recently, we demonstrated that the ethyl alcohol extract of H. fusiforme (EAHF) sensitizes cancer cells to apoptosis through the tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), although no cytotoxicity was reported at low concentrations of EAHF itself [4].…”
Section: Introductionmentioning
confidence: 99%
“…malignant cells. Ethyl alcohol extract of H. fusiforme treatment inhibits tumor metastasis and invasion in Hep3B human hepacocarcinoma cells [23] and sensitizes AGS human gastric adenocarcinoma cells to TNF-related apoptosis-inducing ligand-medicated apoptosis [9]. Another study demonstrated the immunostimulatory and anti-tumor effect of ginsan [24].…”
Section: Effects Of Hfae On the Production Of No And Cytokines In Rawmentioning
confidence: 94%
“…Polysaccharides isolated from plants and algae have been reported to enhance macrophage activation [6][7][8]. A variety of biological activities, including anti-cancer [9] and antiinflammatory [10] activity of H. fusiforme have been reported, but little is known about the molecular mechanism of H. fusiforme as an immunostimulator.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, [16] Ethyl alcohol extract of H. fusiforme was prepared as previously described [12]. Briefly, dried H. fusiforme were extracted in 80% ethyl alcohol at a ratio of 10 ml/g for 24 hr in a refrigerator at 4°C.…”
Section: Introductionmentioning
confidence: 99%